2018
DOI: 10.1002/ece3.4144
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic changes during the invasion of a cosmopolitan species (Phragmites australis)

Abstract: While many introduced invasive species can increase genetic diversity through multiple introductions and/or hybridization to colonize successfully in new environments, others with low genetic diversity have to persist by alternative mechanisms such as epigenetic variation. Given that Phragmites australis is a cosmopolitan reed growing in a wide range of habitats and its invasion history, especially in North America, has been relatively well studied, it provides an ideal system for studying the role and relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 72 publications
(127 reference statements)
2
23
0
Order By: Relevance
“… Amarasinghe et al. (2014) found a global erasure of DNA methylation increased reproductive behavior, Liu et al. (2018) found differences in expression in genes responsible for methylation between castes and Marshall et al.…”
Section: Discussionmentioning
confidence: 99%
“… Amarasinghe et al. (2014) found a global erasure of DNA methylation increased reproductive behavior, Liu et al. (2018) found differences in expression in genes responsible for methylation between castes and Marshall et al.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support previous research which suggests methylation is associated with worker reproductive behaviour. Amarasinghe et al (2014) found a global erasure of DNA methylation increased reproductive behaviour, Liu et al (2018) found differences in expression in genes responsible for methylation between castes and Marshall et al (2019) found differentially methylated genes between B. terrestris castes, some of which were involved in reproductive processes. Numerous other studies have linked methylation to caste differences in various other social insect species, such as; Apis mellifera (Lyko et al , 2010; Elango et al , 2009), Camponotus floridanus and Harpegnathos saltator (Bonasio et al , 2012), Polistes dominula (Weiner et al , 2013) and Zootermopsis nevadensis (Glastad et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They grew populations from different environments under controlled common garden conditions to test the stability of epigenetic inheritance and to partition genetic from epigenetic variation. While they found epigenetic variation to be greater than genetic variation across populations, they did not find convergence in epigenetic markings between populations occupying similar environments, suggesting the relationship between environmentally heritable induced epigenetic variations may not be stable and also dependent on the genetic background (Liu et al, ). In comparison with two saltmarsh species, Foust et al () found while one species showed a significant correlation between epigenetic variation and habitat, the other species did not.…”
Section: Epigenetic Mechanisms a Component Of The Rapid Response To mentioning
confidence: 99%
“…Yet, the relationship between epigenetic variation, population divergence and transgenerational inheritance across environments is not universal. Recently, Liu et al () examined genetic and epigenetic variation of native and invasive lineages of the common reed ( Phragmites australis ) in North America. They grew populations from different environments under controlled common garden conditions to test the stability of epigenetic inheritance and to partition genetic from epigenetic variation.…”
Section: Epigenetic Mechanisms a Component Of The Rapid Response To mentioning
confidence: 99%
See 1 more Smart Citation